Speech-in-Noise Testing: An Introduction for Audiologists - Billings, Curtis J.; Olsen, Tessa M.; Charney, Lauren; Madsen, Brandon M.; Holmes, Corrie E. (Seminars in Hearing, 2023)
Speech-in-noise testing has been proposed as a useful part of the audiometric test battery dating back to the earliest years of the field of audiology. Many speech-in-noise tests have been developed and used to varying degrees. However, multiple barriers have prevented speech-in-noise testing from being used widely in the clinic. The purpose of this article is to provide a resource to audiologists and other hearing health professionals who want to know (1) what tests are available for use, (2) the rationale behind specific tests, and (3) important considerations when selecting one or more tests to use clinically. In addition, data are presented for four speech-in-noise tests with the purpose of comparing outcomes as a function of age and hearing status. The four tests (QuickSIN, Words in Noise [WIN], Listening in Spatialized Noise–Sentences [LiSN-S], and Coordinate Response Measure [CRM]) were completed by 30 individuals from three groups: 10 young adults with normal hearing, 10 older adults with normal hearing, and 10 older adults with hearing loss. The results suggest that, despite significant differences in performance between groups, group overlap was present such that some individuals from one group performed similar to some individuals of other groups; therefore, individual performance was more important than associated group. When selecting an appropriate speech-in-noise test to use clinically, audiologists should carefully consider the purpose of their testing and the type of information they desire as an outcome. A quick-resource table and appendix is provided to aid audiologists and other health professionals in their selection of an appropriate speech-in-noise test.
Keywords: speech-in-noise testing; hearing loss; aging; background noise; audiology; audiometry; QuickSIN; Words in Noise; Listening in Spatialized Noise-Sentences; Coordinate Response Measure